Monitoring the monuments of history –procedure, considerations, threats - Zalasińska, Katarzyna (Protection of Cultural Heritage, 2019)
The significant increase in the number of historic monuments observed in the recent years poses new challenges, entailing the need to create an efficient mechanism for monitoring and managing their condition. This article discusses a system for monitoring historic monuments, which was introduced following the Guidelines of the General Conservator of Monuments dated 19 November 2018. The system aims to enable continual and regular observation concerning the preservation of and the processes which may affect the state of preservation of monuments and their surroundings that have been recognised as historic monuments.